2022
DOI: 10.1108/apjba-07-2021-0303
|View full text |Cite
|
Sign up to set email alerts
|

Efforts are made but food wastage is still going on: a study of motivation factors for food waste reduction among household consumers

Abstract: PurposeThe goal of this research is to find the components that can inspire people to reduce food waste at household consumer level. The components were created by combining the theory of planned behaviour (TPB), theory of interpersonal behaviour (TIB) and motivation opportunity ability (MOA) model.Design/methodology/approachThe study is based on the content analysis, which identifies the motivating factors for food waste reduction at the consumer household level. A total of 12 motivating factors are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Figure 3 shows the distribution of articles from 2013 to 2022. It is observed that CE has started to draw attention from the scientific community consistently, as between 2018 and 2019, several countries experienced food insecurity situations (FAO, 2018(FAO, , 2019, and publications continue to increase each passing year towards finding a global solution to food waste problems, as the issue of food insecurity persists (Matharu et al, 2022). Moreover, the FAO recognises CE as a global model for addressing food system challenges (FAO, 2019).…”
Section: Year Of Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows the distribution of articles from 2013 to 2022. It is observed that CE has started to draw attention from the scientific community consistently, as between 2018 and 2019, several countries experienced food insecurity situations (FAO, 2018(FAO, , 2019, and publications continue to increase each passing year towards finding a global solution to food waste problems, as the issue of food insecurity persists (Matharu et al, 2022). Moreover, the FAO recognises CE as a global model for addressing food system challenges (FAO, 2019).…”
Section: Year Of Publicationsmentioning
confidence: 99%
“…However, despite ongoing efforts, food waste remains a persistent challenge with environmental, economic, and social implications (Matharu et al, 2022;Palansooriya et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research conducted by the European Commission revealed that out of the 88 million tons of food produced annually, households waste 46.5 million tons (Kowalewska and Kołłajtis-Dołowy, 2018). Before reaching retail markets, approximately 13.3% of the world's food is lost, known as food loss (mostly occurs in developing nations), and at the consumer level, 17% is wasted, known as food waste (mostly occurs in developed nations) (Matharu et al, 2022;United Nations, 2022). According to the United Nations report on sustainable development goals (United Nations, 2022), this estimate of 17% is approximately 931 million metric tons which are available for consumption but wasted in households (61%), food service (26%), and retail levels (13%) (UNEP, 2021), equal to 121 kg per person per year.…”
Section: Introductionmentioning
confidence: 99%
“…Each country will only be known to be food secure if its population can access sufficient, safe, and nutritious food (Aktas et al, 2018;. This goal will necessitate minimising food waste whilst benefiting people and the planet (Matharu et al, 2022;United Nations, 2022). Global food security within a sustainable environment is needed for an hour (Koester, 2017).…”
Section: Introductionmentioning
confidence: 99%